Perbedaan Tingkat Kecemasan Orang Tua Anak Penderita Leukemia Sebelum dengan Sesudah Kemoterapi - Suchi Aulia Nur Silmi; Ieva B. Akbar; Sara Puspita (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Acute lymphoblastic leukemia (ALL) is children's most common type of cancer. Acute lymphoblastic leukemia can be cured with chemotherapy. The initial treatment for ALL is induction chemotherapy, lasting 4–6 weeks using 3 or 4 drugs. Parents who have children with ALL will experience anxiety, especially mothers. This study aims to analyze the differences in the anxiety levels of parents of children with acute lymphoblastic leukemia before and after the induction phase of chemotherapy. The research was conducted in July–October 2022. The research method is a comparative research design with a longitudinal study approach. The sample of this study was 45 people using a total sampling technique on the parents of children with ALL at Al-Islam Hospital in Bandung. Data collection was carried out using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis used the McNemar test. The results showed that 28 mothers experienced severe–very severe levels of anxiety before the induction phase of chemotherapy, and 28 experienced mild–moderate anxiety levels after the induction phase of chemotherapy. The results of the McNemar test obtained a value of p=0.001 (p<0.05). In conclusion, parents' anxiety in children with ALL increased before chemo and tended to decrease after the induction phase of chemotherapy. Abstrak. Leukemia limfoblastik akut (LLA) merupakan jenis kanker yang paling banyak terjadi pada anak. Leukemia limfoblastik akut dapat disembuhkan dengan kemoterapi. Terapi awal LLA yaitu kemoterapi fase induksi, berlangsung 4–6 minggu menggunakan 3 atau 4 obat. Orangtua yang memiliki anak LLA akan mengalami kecemasan terutama ibu. Penelitian ini bertujuan menganalisis perbedaan tingkat kecemasan orangtua anak penderita leukemia limfoblastik akut sebelum dengan sesudah kemoterapi fase induksi. Penelitian dilakukan pada bulan Juli–Oktober 2022. Metode penelitian adalah desain penelitian komparatif dengan pendekatan studi longitudinal. Sampel penelitian ini adalah 45 orang dengan teknik total sampling pada orangtua anak penderita LLA di RS Al-Islam Bandung. Pengumpulan data dilakukan menggunakan kuesioner Hamilton Anxiety Rating Scale (HARS). Analisis data menggunakan uji McNemar. Hasil penelitian menunjukan ibu mengalami tingkat kecemasan berat–sangat berat sebelum kemoterapi fase induksi sebanyak 28 dan mengalami tingkat kecemasan ringan–sedang sesudah kemoterapi fase induksi sebanyak 28. Hasil uji McNemar didapatkan nilai p=0,001 (p<0,05). Simpulan, kecemasan orangtua pada anak penderita LLA meningkat sebelum kemoterapi dan cenderung menurun sesudah kemoterapi fase induksi.